The Correlation Between Grammar Mastery and Writing Thesis Proposal at STKIP YDB Lubuk Alung - Siska Okta Widya; Irna Wahyuni (JURNAL ARBITRER, 2018)
This research was conducted to: (1) identify proficiency level of Grammar Mastery English department Students, (2) Identify proficiency level of writing thesis proposal English department Students, (3) Investigate the correlation between Grammar mastery and Writing Thesis Proposal of English Language Education Program at the sixth semester at STKIP YDB Lubuk Alung. The research applied correlational research; the population of this research was the sixth-semester students in academic year 2017/2018. The samples of this research were 32 students chosen by using total sampling technique. The data were analyzed by using descriptive and inferential statistic through SPSS 22.0 version. The research result showed that (1) the students’ grammar mastery was proven by mean score 73.84, it was classified as a moderate category, (2) the students writing proposal thesis was proven by mean score 74.75, which is categorized as moderate. (3) There was a correlation between Grammar mastery and Writing Thesis Proposal of English Language Education Program. It showed that the value of Fcount= 0.837was greater than Ftable= 0.349 (Fcount > Ftable), or p= 0.000 was lower than α= 0.05 (p <α). In other words, the alternative hypothesis that saying there is a significant relationship between grammar mastery and writing thesis proposal is accepted. It can be concluded that grammatical mastery gives a significant contribution to the paper thesis writing.